Exchange Rate Volatility, Financial Constraints and Trade: Empirical Evidence from Chinese Firms - Jérôme Héricourt; Sandra Poncet (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies how firm-level export performance is affected by Real Exchange Rate (RER) volatility and investigates whether this effect depends on existing financial constraints. Our empirical analysis relies on export data for more than 100,000 Chinese exporters over the 2000-2006 period. We confirm a trade-deterring effect of RER volatility. We find that the firms' decision to start exporting and the exported value decrease for destinations with a higher exchange rate volatility and that this effect is magnified for financially vulnerable firms. As expected, financial development seems to dampen this negative impact, especially on the intensive margin of export. These results provide micro-founded evidence suggesting that the existence of well-developed financial markets allow firms to hedge exchange rate risk. They also support a key role of financial constraints in determining the macro impact of RER volatility on real outcomes.
Keywords: F14; F31; L25; 330; exchange rate volatility; financial development; exports